Two Sides, Same Coin: Posttraumatic Growth Among Selected Nurses with History of Covid-19 Virus in Bataan, Philippines - Ronnel Magpantay; Jayvie Villazor (Indonesian Journal of Global Health Research, 2025)
Over the past three years, the pandemic has substantially altered the field of healthcare. Consequently, the general well-being of nurses was negatively impacted as a result of this change. It affects both their professional and personal lives, specifically their psychological, social, and physical sequelae. However, positive transformation, also known as posttraumatic growth, is possible. In the current study, the objective is to provide an account and analysis of the essence of the experience of posttraumatic growth among nurses after being exposed to COVID-19 during the pandemic. Twelve participants from Bataan, Philippines, were interviewed in person using a semi-structured interview format based on descriptive phenomenology. The study's findings unveiled three distinct themes, each of which possesses its own complementary opposition. One of the dichotomies is referred to as "heads," while the other is known as "tails" to represent the idea of "two sides of the same coin." The three dichotomies are spirituality vs. uncertainty, affinity vs. incompatibility, and prosperity vs. adversity. The findings will provide mental health providers with guidance regarding the causes and conditions that promote posttraumatic growth. Furthermore, the aforementioned research will contribute valuable insights into the areas of nursing, clinical psychology, and positive psychology in the Philippines.